Pemetaan Jalur Jalan Wisata Bukit Jamur di Kabupaten Bengkayang Menggunakan Sistem Informasi Geografis (SIG) - Erni Yuniarti; Meta Indah Fitriani; Tita Khairiyah (TATALOKA, 2021)
Bukit  Jamur  is  located  in  a  strategic  area  near  Bengkayang  Urban  and  is  an  urban tourism  icon  that  is  popular  with  visitors  to  do  light-scale  hiking.  Although  located  near  urban areas, there are no information boards so visitors are not aware of the existence of tourist sites and the lack of road directions both in the village and on the hiking trails. In addition, inadequate road infrastructure  makes  visitors  feel  uncomfortable.  The  delivery  of  information  with  a  map  is expected  to  make  it  easier  for  visitors  to  know  the  initial  condition  of  the  tourist  location.  The purpose  of  this  research  is  to  map  the  road  to  tourist  sites  equipped  with  road  signs  and information boards so that visitors can know the route clearly. The analysis method in this research uses the method of implementing Geographic Information System (SIG). The findings in the field stated that there are 2 village road paths, namely  the Belangko Hamlet road and the Dusun Jaku Bawah road path that is still lacking road directions and there are 3 hiking paths, namely stairways cliff paths and weeds that have not been equipped with directions and information boards so that there needs to be additional directions and information boards in the village and climbing.